2009
DOI: 10.1021/cm900682q
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Catalytic Study of Solid Solution of GaN in ZnO

Abstract: Solid solutions of GaN in ZnO (Zn 1-z Ga z )(O 1-x N x ) (x and z e 0.15) have been prepared by simple solution combustion method. Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn 1-z Ga z )(O 1-x N x ). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 38 publications
7
63
0
Order By: Relevance
“…Little compositional mixing is necessary to achieve visible absorption, which is observed at both ends of the composition range, in agreement with previous observations in bulk (Ga 1Àx Zn x )(N 1Àx O x ), 14,25,27,30,36,37 although the appearance of the spectra is qualitatively different at the two ends of the range. By examining the temperature-dependence of nitridation of ZnGa 2 O 4 under NH 3 , we found that, at the relatively low synthesis temperature of 650 C, inclusion of ZnO in the starting material is necessary to obtain wurtzite (Ga 1Àx Zn x )(N 1Àx O x ).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Little compositional mixing is necessary to achieve visible absorption, which is observed at both ends of the composition range, in agreement with previous observations in bulk (Ga 1Àx Zn x )(N 1Àx O x ), 14,25,27,30,36,37 although the appearance of the spectra is qualitatively different at the two ends of the range. By examining the temperature-dependence of nitridation of ZnGa 2 O 4 under NH 3 , we found that, at the relatively low synthesis temperature of 650 C, inclusion of ZnO in the starting material is necessary to obtain wurtzite (Ga 1Àx Zn x )(N 1Àx O x ).…”
Section: Introductionsupporting
confidence: 91%
“…44 The products at each end (0.06 and 0.98) have E g values of 2.9 and 2.6 eV, respectively. 25 Remarkably, the visible absorption is still relatively strong even when x ¼ 0.98, i.e., almost pure ZnO (Fig. 14,25,27,30,36,37 At the low-x end of the composition range, the diffuse reectance spectra have similar shapes, with the effect of the composition being simply the red shiing of the spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, recent researches have shown that incorporating one material into the other could significantly reduce the band gap. Maeda et al 3 reported that randomly incorporating ZnO into GaN host (with 22% ZnO) reduces the optical band gap to 2.60 eV, and randomly incorporating GaN into ZnO host (with 15% GaN) reduces the optical band gap to 2.50 eV 4. Huda et al 5 also have shown that this band gaps reduction is not symmetric, that is, incorporating GaN in ZnO host (with 1.85% GaN) reduces the band gap much more than that of incorporating ZnO in GaN host (with 1.85% ZnO) based on theoretical calculation.…”
Section: Introductionmentioning
confidence: 99%